Assessment of Knowledge, Attitudes, and Practices of Medical Waste Management for Healthcare Providers in Two of Government Hospitals in Karbala, Iraq - Dunia Fawaz Mohammed; Muhannad Sabah Aber; Seror kadhim hamza (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Background: Medical waste is a significant health danger and environmental pollution problem due to its hazardous composition. The expertise and practice of healthcare staff in the proper removal of medical waste is essential for good medical waste management. The purpose of this study was to analyze the knowledge, attitudes, and practices related to medical waste management among healthcare workers in hospitals in Karbala/Iraq. Materials and Methods: descriptive cross-sectional study was conducted using a questionnaire distributed to health care providers in two selected hospitals in Karbala/ Iraq. Results: The results showed the good level of knowledge, attitudes and practices of healthcare providers towards medical waste. There is statistical significance between health care providers' knowledge, attitudes and practices towards medical waste, and their educational level and training courses. In addition to the recording of the statistical significance that were between knowledge with attitudes and practices. The levels can be categorized as positive but it is important to focus on increasing and improving the training of health care providers as it is the basis of the medical waste treatment process. Conclusion: increasing knowledge is one of the best tools to maintain proper workflow in isolating medical waste and maintaining the safety of employees, patients, and the environment.